2014
DOI: 10.5993/ajhb.38.6.3
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and HIV Risk among College Students

Abstract: Findings indicate low rates of HIV testing and communication with a partner about HIV, suggesting the importance of sexual health intervention and education programs for college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…Previous research has shown that daily use of PrEP is associated with reduced sexual anxiety and improved levels of satisfaction and esteem, which may have a positive influence on body image satisfaction and reduced risk for ON [39]. Those men who participate in regular HIV-prevention strategies such as a frequency for HIV testing have been found to be engage in greater use of PrEP, and men who self-report a healthier level of body image satisfaction may be more inclined to speak with their partners about HIV-testing habits [40][41][42]. However, it is important to note that this reduction in the risk for ON is only true in multivariate analyses, and that the influence of occasional use on increased risk for ON was only found in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that daily use of PrEP is associated with reduced sexual anxiety and improved levels of satisfaction and esteem, which may have a positive influence on body image satisfaction and reduced risk for ON [39]. Those men who participate in regular HIV-prevention strategies such as a frequency for HIV testing have been found to be engage in greater use of PrEP, and men who self-report a healthier level of body image satisfaction may be more inclined to speak with their partners about HIV-testing habits [40][41][42]. However, it is important to note that this reduction in the risk for ON is only true in multivariate analyses, and that the influence of occasional use on increased risk for ON was only found in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, fewer sex partners may not be indicative of better sexual health among women. Although fewer sex partners means less risk for unplanned pregnancy and STDs, it may represent feeling less empowered and deserving of healthy sexual experiences, which can impact the confidence and assertiveness required for communication about sex and contraception (Gillen & Markey, 2014; Landor & Ramseyer Winter, 2019). Consequently, promoting body positivity regardless of body size could enhance the sexual health of all women and men, including those who misperceive their weight.…”
Section: Discussionmentioning
confidence: 99%
“…46 Those men who participate in regular HIV-prevention strategies such as a frequency for HIV testing have been found to be engage in greater use of PrEP, and men who self-report a healthier level of body image satisfaction may be more inclined to speak with their partners about HIV-testing habits. [47][48][49] However, it is important to note that this reduction in the risk for ON is only true in multivariate analyses, and that the in uence of occasional use on increased risk for ON was only found in univariate analyses. The role of PrEP, therefore, probably requires a more careful study.…”
Section: Discussionmentioning
confidence: 99%